Comparing Percutaneous Vertebroplasty and Conservative Therapy for Treating Osteoporotic Compression Fractures in the Thoracic and Lumbar Spine: A Systematic Review and Meta-Analysis. (15th June 2016) - Mattie, Ryan; Laimi, Katri; Yu, Sloane; Saltychev, Mikhail
Abstract : Background: Vertebral compression fractures are a common complication of osteoporosis and are often treated by percutaneous vertebroplasty (PVP). The ability of this procedure to relieve pain better than conservative treatment is still debated. The purpose of this study was to compare the degree and duration of pain relief following PVP with that following conservative treatment for osteoporotic compression fractures by means of meta-analysis of randomized controlled trials. Methods: The CENTRAL (Cochrane Central Register of Controlled Trials), MEDLINE, Embase, CINAHL (Cumulative Index to Nursing and Allied Health Literature), and Web of Science databases were queried for randomized controlled trials comparing PVP with conservative treatment or placebo/sham. The methodological quality was assessed according to the Cochrane Collaboration's domain-based evaluation framework. Random-effects meta-analysis of the raw mean difference between groups in change in pain level was performed, with sensitivity analyses and the Egger test for potential publication bias. Results: Of 209 records found, 11 were considered relevant, involving 1, 048 participants. The risk of bias was considered low in 10 studies and high in 1. The 531 patients treated with PVP had a significantly lower pain level compared with the control group at 1 to 2 weeks, 2 to 3 months, and 12 months. The 95% CI (confidence interval) of the pooled effect size at every time interval included the score of 1.5, considered to be the minimal clinically important difference. The largest pooled effect size of −1.4 (95% CI, −2.3 to −0.5) was found during the first 1 to 2 weeks. The heterogeneity was high at all 3 time points (I2, 71% to 96%). No significant publication bias was detected. Conclusions: Up to 1 year postoperatively, the effect of PVP exceeded the effect of conservative therapy with respect to pain relief in patients with osteoporotic compression fractures. The effect size was significant and close to the minimal clinically important difference.